Validasi Skor Skrining COVID-19 RSUP Dr. Sardjito Yogyakarta - Ulfa, Dinda; Sari, Djayanti; Kurniawati, Juni (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2021)
Background: Dr. Sardjito’s hospital Covid-19 screening score is a tool to assess patients who are suspected of being infected using RT-PCR swab examination. Unfortunately, there has never been researched regarding the validity. Objective: Validating the Dr. Sardjito’s hospital Covid-19 screening score to assess patients suspected of Covid-19 infection which was confirmed by the results of the RT -PCR swab at the Dr. Sardjito Hospital Yogyakarta. Method: This study used an observational retrospective cohort design. Patients who were included in the inclusion criteria were those aged >18 years, from 24th April 2020 to 31th December 2020. Result: The number of study samples was 705 patients. Discrimination ability of Dr. Sardjito’s hospital Covid-19 screening scoring was assessed by AUC and the result was 0,556 (CI 95%: 0,51-0,61. Calibration ability obtained HL test value p=0.001 (p<0.05). Conclusion: Dr. Sardjito’s hospital Covid-19 screening scoring has a very weak discrimination ability and poor calibration, so the Dr. Sardjito’s hospital Covid-19 screening scoring is invalid in predicting the results of RT-PCR swab at Dr. Sardjito Hospital Yogyakarta.